Wisdom in transition: act and consequence in Second Temple instructions - Adams, Samuel L. (Supplements to the Journal for the study of Judaism, 2008)
This volume considers a major shift among Jewish sages during the Second Temple period, as certain authors moved from an earthly focus to a belief in individual immortality. Egyptian instructions and the book of Proverbs are examined for necessary background. The colorful responses of Qoheleth and Ben Sira to an emergent belief in the afterlife are also discussed. 4QInstruction, the largest Wisdom text from the Dead Sea Scrolls corpus, demonstrates this shift to an eschatological understanding. This book considers the diverse reasons for the changes that one finds in 4QInstruction, especially